أحاديث فضيلة الزهد في كتاب سَيْر السالكين للشيخ عبد الصمد الفَلِمْبَانِي دراسة تحليلية نقدية - Hidayat, Taufiq - (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2020)
This research examines the Hadith Zuhud (Asceticism) in the Sayr Al-Salikiin of Abdus Somad Al-Falimbani in terms of matn (their text) and sanad (chain of narration). A brief introduction of the narrator of the hadith is also given. Attestation of the hadith in other books is examined and the status of hadith is determined, whether they remain daif (weak) or upgraded to be hasan (valid). The researcher used the inductive method to collect hadith Zuhud (Asceticism) in the Sayr Al-Salikiin of Abdus Somad Al-Falimbani as well as the critical approach on the attestation in other books and determine the status of the hadith and used the analytical method to conclude on some jurisprudence of the Hadith. As a result, the researcher found most of hadith in the Sayr Al-Salikiin are eligible to be upgraded into hasan. The rest remain daif due the unavailable attestation or weak narrator chain. The hadiths in the Sayr Al-Salikiin book about Zuhud (Asceticism) are thirty. But, The hadiths about advantages of asceticism five. hadiths that reach to the hasan level are one. And the rest remain daif due the unavailable attestation in another book or weaken narrator.